Childfree Perspektif Quraish Shihab: Analisis Tafsir Al-Mishbah terhadap QS. Al-Baqarah Ayat 233 - Tegar Daffa Al Firdaus; Bunga Septia Nurul Fatikhah; Al Dafa Nurrohman; Pupung Budi Kurniawan (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
The phenomenon of childfree as a conscious decision not to have children has become a growing issue in modern society, including among Indonesian Muslims. This study aims to examine M. Quraish Shihab's perspective on the concept of childfree through an analysis of QS. Al-Baqarah verse 233 in the Tafsir Al-Mishbah. The research employs a qualitative method using a thematic exegesis (maudhu‘i) approach and content analysis. The primary source is Tafsir Al-Mishbah, supported by relevant secondary literature. The results indicate that QS. Al-Baqarah verse 233 emphasizes the significance of children's presence in marriage as a trust and as part of the Islamic legal objective (maqāṣid al-sharī‘ah), particularly in preserving lineage (ḥifẓ al-nasl). According to Quraish Shihab, both mother and father share responsibilities in breastfeeding and financial support to ensure a child's optimal growth. A permanent decision to remain childfree, especially without a legitimate religious reason, contradicts these core Islamic principles. This study concludes that the childfree choice must be critically examined and should not disregard the spiritual and social responsibilities inherent in the Islamic family institution.